Metabolic Reprogramming and Immune Evasion in Nasopharyngeal Carcinoma - Huang, Huimei; Li, Shisheng; Tang, Qinglai; Zhu, Gangcai (Frontiers in Immunology, 2021)
Nasopharyngeal carcinoma (NPC) is a malignant tumor of the nasopharynx mainly characterized by geographic distribution and EBV infection. Metabolic reprogramming, one of the cancer hallmarks, has been frequently reported in NPCs to adapt to internal energy demands and external environmental pressures. Inevitably, the metabolic reprogramming within the tumor cell will lead to a decreased pH value and diverse nutritional supplements in the tumor-infiltrating micro-environment incorporating immune cells, fibroblasts, and endothelial cells. Accumulated evidence indicates that metabolic reprogramming derived from NPC cells may facilitate cancer progression and immunosuppression by cell-cell communications with their surrounding immune cells. This review presents the dysregulated metabolism processes, including glucose, fatty acid, amino acid, nucleotide metabolism, and their mutual interactions in NPC. Moreover, the potential connections between reprogrammed metabolism, tumor immunity, and associated therapy would be discussed in this review. Accordingly, the development of targets on the interactions between metabolic reprogramming and immune cells may provide assistances to overcome the current treatment resistance in NPC patients.